Strategies to improve the quality of wheat flour in baking: a review - Mariana de Paula Kraüss Ferreira; Vitor Anselmo da Guia Ribeiro; Jefferson Henrique Tiago Barros; Caroline Joy Steel (Brazilian Journal of Food Technology)
Abstract The different bakery products consumed worldwide require wheat flour with specific viscoelastic characteristics, which are not always available on the market. To meet these particular demands, wheat flour mills and baking industries turn to ingredients, additives, and processing aids. These improving agents act on the gluten network and other flour components, adapting them to produce various products with the desired technological and sensory properties. Many studies relate increases in the parameters obtained in flour quality analyses, such as farinographic, extensographic, alveographic, and others, with the flour-strengthening effect of various ingredients, additives, and processing aids used; however, this is not a direct relationship. In this review, we evaluated each strategy for improving wheat flour, considering key studies in the field of baking, and examining how these strategies work. Focusing on gluten, which is crucial for the technological quality of the flour, we explored strategies involving additives (oxidizing agents, emulsifiers, and hydrocolloids), processing aids (enzymes), and the ingredient vital wheat gluten. We also evaluated the regulatory aspects governing the use of these enhancers in various countries.